2019
DOI: 10.1016/j.copsyc.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficits in Amblyopia

Abstract: Amblyopia is a neuro-developmental abnormality associated with deficits in a broad range of both lowand high-level visual tasks. This is particularly true in strabismic amblyopia where fixation is unstable and there is an increased frequency of microsaccades. In light of the close association between eye movements and attention, we propose a novel hypothesis: that the cost of unstable fixation in amblyopia is a deficit in selective attention. The increased latency for saccades and manual response time with amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 57 publications
0
30
0
2
Order By: Relevance
“…Another recent proposal suggests that fixational instability that is especially common in strabismic amblyopic observers produces abnormal selective attention (Verghese et al, 2019). The idea draws from considerable evidence that eye movements and attention are closely linked.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent proposal suggests that fixational instability that is especially common in strabismic amblyopic observers produces abnormal selective attention (Verghese et al, 2019). The idea draws from considerable evidence that eye movements and attention are closely linked.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, most have only inferred the role of attention in each of their tasks without directly manipulating it (see [16,17] for more details). More recently, it has been hypothesized that increased fixation instability (particularly for strabismics) leads to higher rates of microsaccades, or fixational eye movements <1°, which results in an amblyopic deficit in selective attention [54]. However, there is controversy as to whether amblyopes reliably generate higher rates of microsaccades (see Discussion of [18]).…”
Section: Concomitant Gains In Visual Acuitymentioning
confidence: 99%
“…Consequently, the brain suppresses the visual information coming from the affected amblyopic eye (interocular suppression), which impairs the fusion of images needed for binocular vision (Bretas & Soriano, 2016). Losses in contrast sensitivity and visual acuity are a landmark of the amblyopic eye (Hess & Howell., 1977;Levi & Harwerth, 1977); however, amblyopic individuals show a range of sensory and oculomotor deficiencies, including higher level deficits (for recent reviews see Kiorpes & Daw, 2018, Levi, 2020Verghese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1962, Van Balen & Henkes suggested that the amblyopic eye was "inattententive", and Singer (1982) pointed to the crucial role of attention in the development of amblyopia and reported that synchronous binocular eye movements are essential for the development of normal visual pathways (Ciuffreda et al, 1979a(Ciuffreda et al, , 1979b. Impaired eye movements, such as poor fixation stability and an increased frequency of microsaccades as observed in human observers with amblyopia have been suggested to not only impact visual perception, but also the spatial allocation of selective attention (Verghese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation